Characterization of children’s prospective prescription review and exploration of factors influencing the success of interventions - Qiang Wen; Chuang Yang; Bangjian Deng; Yi Zhang; Lin Song (Therapeutic Advances in Drug Safety)
Background: Medication safety is crucial in clinical care. Although many hospitals have implemented prospective prescription review systems to manage medication use, the impact of these systems on pediatric patients is not yet fully understood. Objectives: We explore the characteristics and economic impacts of pediatric prospective prescription review and identify factors influencing intervention success rates. Design: This study adopted a cross-sectional design. Methods: Prospective prescription review tasks were compared in the outpatient of our hospital between 2021 and 2023 to assess medication rationalization rates and cost variability. Data were collected using the PASS PharmReview system, including patient information, medication indications, prescribing physicians, intervention pharmacists, prescription rationality rate, and medication costs. SPSS 26.0 software was used to compare changes in medication rationality and medication costs between the initial (2021) and stable (2023) periods and to analyze factors affecting intervention success during the stable period by the logistic regression model. Results: The study included 11,533,807 prospective prescription review tasks. The medication rationalization rate increased from 92.0% to 95.7% ( p  < 0.05) between the initial ( n  = 5,392,551) and stabilization periods ( n  = 6,141,256). Outpatient medication costs per capita decreased by 3.2%, from ¥320.7 to ¥310.5. Factors influencing intervention success included the following: the greater age is negatively associated with success( p  < 0.001, odds ratio (OR) = 0.98); internal medicine demonstrates a superior intervention success rate compared to the surgical department ( p  < 0.001, OR = 1.37); higher physician titles were associated with lower success rates ( p  < 0.001, OR = 0.59); and success increased with pharmacists of higher educational levels ( p  < 0.001, OR = 1.18). Conclusion: Implementing a prospective prescription review system in pediatric outpatient settings improves medication rationality and reduces errors and costs, with intervention success influenced by patient age, department, physician titles, and the educational level of pharmacists.